PERLINDUNGAN HUKUM TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DALAM TINDAK PIDANA PENGANIAYAAN BERAT (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 3202 K/PID.SUS/2023) - Irwika Fadhila Tanjung (Fakultas Hukum Universitas Borobudur, 2024)
The presence of children in society needs attention so that their actions do not go beyond the limits that can harm others and themselves. Many incidents show that lack of control has resulted in juvenile delinquency escalating into criminal acts or violations of the law, so that such behavior cannot be tolerated. This study discusses the application of the law to perpetrators of criminal acts of serious abuse against minors and the judge's considerations in imposing criminal sanctions on minors who commit criminal acts ofserious abuse in Decision Number 3202 K/Pid.Sus/2023. This study uses a normative legal research method by examining secondary data. The results of the study explain that the application of the law to perpetrators of criminal acts of serious abuse against minors in Supreme Court Decision Number 3202 K/Pid.Su/2023 is appropriate because the actions of the defendant AG were proven legally and convincingly guilty of participating in serious abuse resulting in serious injuries, and fulfill the elements of Article 355 paragraph(1) of the Criminal Code in conjunction with Article 55 paragraph (1) number 1 of the Criminal Code. The basis for the judge's consideration in sentencing the defendant AG was that the act of serious assault committed by the defendant AG was proven legally and convincingly to be a premeditated crime that resulted in serious injury so that the defendant AG was sentenced to 3 years and 6 months in prison (Article 355 paragraph (1) in conjunction with Article 55 paragraph (1) point 1 of the Criminal Code). The judge's consideration in the trial was based on the fact that the actions of the defendant AG had fulfilled the elements charged by the public prosecutor. The judge had also reviewed and considered written evidence and expert testimony from the defendant AG's lawyer.